Pelaksanaan Program Penguatan Pengembangan Karakter Melalui Kegiatan Pembiasaan Dalam Peningkatan Mutu Sekolah - Suryana, Suryana; Kusen, Kusen; Sumarto, Sumarto (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
This research aims to examine aspects of character development programs through habituation activities, focusing on design, implementation, school community involvement, and identifying potential obstacles. The study took place at SMA Negeri 1 Rejang Lebong with a qualitative research approach and a case study design. Data collection methods included interviews, observations, and documentation. Data analysis was conducted through reduction, presentation, and inference. Research findings include: socialization planning for Competency Standards (SKL), implementation of habituation activities in classrooms and the school, and the involvement of caregivers, mentors, and teachers in the Character Development Strengthening Program (PPC). The participation of students, instructors, institutions, and the school board, besides parents, is identified as key factors that can influence or deactivate the learning environment. These findings can guide the development of similar programs in other schools to enhance the quality of character education.